ENHANCING GEN Z’S SENSORY EXPERIENCE THROUGH MULTI-SENSORY SOCIAL SPACE DESIGN - Brian Edgar; Srinaga, Felia; Jacky Thiodore (Jurnal Strategi Desain dan Inovasi Sosial, 2024)
Human existence has long been intertwined with nature and its elements. Before modernization and technology became part of our daily lives, our five senses (sight, hearing, smell, touch, and taste) helped us perceive and interact with the world. However, in today’s digital era, we are increasingly disconnected from our environment. Our attention is consumed by screens, dominated by all things digital leading to a diminished awareness of the world around us. This disconnection is especially evident among Generation Z, who were “born to be digital”. They may not fully appreciate the value of sensory experiences, relying on technology as a substitute. This impacts their well-being through cognitive, affective, and psychomotor aspects. Recognizing this, author proposes the design of a social space that is intended on rebuilding and reestablishing human sensory connections, especially for Generation Z, with their environment through three aspects: humans with nature and environment, with each other, and with themselves. The design of a multi-sensory social space serving as a third place for Generation Z is identified through theoretical studies, precedent studies, and questionnaires. The research results were implemented into the design through activities and programs to enhance specific sensory experiences. Consequently, design strategies include site design, access & circulation, space program & activity zoning, building massing, facade & opening, interior planning, and open space & green pattern planning.Additionally, site identification of Pondok Ranji, Bintaro was undertaken in hopes to restore the holistic relationship between humans and their environment.